Stock exchange: theory and practice - I. P. Akimova; A. V. Vlasov (Путеводитель предпринимателя, 2020)
The development of modern market trade has changed radically over the past 15 years. Digital tools «collapsed» state borders and thus new forms of trade were opened, among them trade on the stock exchange. The article discusses some theoretical and practical aspects of trading on stock exchanges. An analysis of existing practices, typical errors and the possibility of eliminating them.